Abnormal peri-pubertal anthropometric measurements and growth pattern in adolescent idiopathic scoliosis: a study of 598 patients - Siu King Cheung, Catherine; Tak Keung Lee, Warren; Kit Tse, Yee; Ping Tang, Sheng; Man Lee, Kwong; Guo, Xia; Qin, Lin; Chun Yiu Cheng, Jack (Spine (Philadelphia, Pa. 1976), 2003)
A cross-sectional study of anthropometric parameters in adolescent idiopathic scoliosis (AIS). To compare anthropometric parameters and growth pattern of AIS girls versus normal controls during peri-puberty. Abnormal pattern of growth has been reported in AIS patients. The sequential changes of growth and the correlation with curve severity have not been properly studied. Five hundred ninety-eight AIS girls and 307 healthy girls entered the study. Weight, height, body mass index (BMI), arm span, sitting height, and leg length were determined using standard techniques. Height and sitting height were adjusted by using the greatest Cobb angle to correct for spinal deformity (Bjure's formula). Puberty was graded by Tanner's staging. AIS girls had significantly shorter height (P = 0.001), corrected height (P = 0.005), arm span (P = 0.022), sitting height (P = 0.005) and leg length (P = 0.004) than the controls at pubertal stage I. From pubertal stages II through V, corrected height (P <or= 0.033) and arm span (P <or= 0.038) were significantly longer in the AIS than controls. Corrected sitting height was also longer in AIS from stages II through IV (P <or= 0.043). Furthermore, BMI of AIS was significantly lower than that of controls from stages II through IV (P <or= 0.038). In addition, significant correlations of the curve severity versus weight, BMI, and arm span were also found (P <or= 0.048). Various body segmental lengths were initially significantly shorter in AIS before puberty. However, after the onset of puberty, significantly longer corrected height, arm span, and various body segments were found. And there were significant correlations between anthropometric parameters and the scoliotic curve severity. Results of this large-scale study revealed the presence of abnormal growth in AIS patients during peripubertal development.